Need of a Comprehensive and Feasible Psychometric Test in the Assessment of Perinatal Mental Health - A Systematic Review - Maj Anupa Devi Kairy; Sneha Bharadwaj; Kajal Tomar; Dr. Deepika Chamoli Shahi (International Journal of Behavioral Sciences, 2026)
The perinatal period is a period of happiness as well as hardships. A woman undergoes many psychological changes during this period which makes her prone to mental health disorders that can be detrimental to the health of the women and her child. Its essential to detect these disorders as early as possible and hence a psychometric test or tool which is easy to administer and interpret is needed. Globally various tools are available for use in perinatal period. The aim of this study is to assess the need of a comprehensive and feasible psychometric test in the assessment of perinatal mental health. We searched databases like Google scholar, PubMed, Web of Science, Springer, Elsevier. Research articles on various tools used in assessment of perinatal mental health disorders were reviewed. We have gone through 105 papers and identified 50 such articles which spoke about various tools used globally for screening perinatal mental health disorders for our systematic review. We reached the conclusion that there is no set standard for which tool to be used, time and frequency of administration and validation of tools to be used in various settings.
Keywords: EPDS; perinatal depression and anxiety; perinatal mental health disorders; perinatal period; psychometric tools/tests